2011
DOI: 10.4103/0019-5154.80413
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo: A review of some facts lesser known about depigmentation

Abstract: Vitiligo is a disorder that causes the destruction of melanocytes. It has three important factors underlying this destruction. The depigmented skin has many aberrant functions such as a muted response to contact allergens, a phenomenon also seen in mice that depigment. The white skin of those with vitiligo does not form non-melanoma skin cancers although the white skin of albinos, which has a similar color as vitiligo, is highly susceptible to skin cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 57 publications
(59 reference statements)
1
29
0
Order By: Relevance
“…mysterious features of vitiligo is the resistance of skin depigmented by vitiligo to producing skin cancers. 12 In one study it was concluded that vitiligo is skin manifestation of an internal disease. 13 This study on eighty cases of childhood vitiligo will cover the epidemiology and clinical spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…mysterious features of vitiligo is the resistance of skin depigmented by vitiligo to producing skin cancers. 12 In one study it was concluded that vitiligo is skin manifestation of an internal disease. 13 This study on eighty cases of childhood vitiligo will cover the epidemiology and clinical spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Tobin et al observed that discolored skin is not completely deprived of melanocytes and that they may, in vitro, regain their functions [15]. For this purpose, bovine catalase was added to the culture medium of melanocytes obtained from discolored patches, to deactivate reactive oxygen species [16,17]. A similar phenomenon was observed after in vivo administration of pseudocatalase activated earlier with narrowband UVB radiation, which was also associated with inactivation of reactive oxygen species [17].…”
Section: Vitiligo and Skin Cancersmentioning
confidence: 92%
“…It mainly involves antityrosinase antibodies and infiltrating CD8+ oligoclonal T cells. It is assumed that these actions lead to the destruction of melanocytes during the immune response to MM antigens [16]. Genetic studies indicate a mutually exclusive relationship of melanoma and vitiligo (the SNP alleles in the TYR gene are related to vitiligo and the minor alleles to melanoma) [18].…”
Section: Vitiligo and Skin Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…The QoL assessments, evaluating topics such as interpersonal relations, disease limitations, daily activities, occupational function and sexuality, reflect the problems patients experience [3,4]. Other factors affecting the self-esteem (SE) and QoL are psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%